2017
DOI: 10.1038/cdd.2016.150
|View full text |Cite
|
Sign up to set email alerts
|

N-glycosylation of mouse TRAIL-R and human TRAIL-R1 enhances TRAIL-induced death

Abstract: APO2L/TRAIL (TNF-related apoptosis-inducing ligand) induces death of tumor cells through two agonist receptors, TRAIL-R1 and TRAIL-R2. We demonstrate here that N-linked glycosylation (N-glyc) plays also an important regulatory role for TRAIL-R1-mediated and mouse TRAIL receptor (mTRAIL-R)-mediated apoptosis, but not for TRAIL-R2, which is devoid of N-glycans. Cells expressing N-glyc-defective mutants of TRAIL-R1 and mouse TRAIL-R were less sensitive to TRAIL than their wild-type counterparts. Defective apoptot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
86
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 81 publications
(89 citation statements)
references
References 41 publications
3
86
0
Order By: Relevance
“…Here we further show that this insensitivity is not related to a lack of surface expression levels of DR5, but to a specific lack of fucosylation. This finding is in line with earlier observations that TRAIL-sensitive colon adenocarcinoma cell lines show relatively high mRNA levels of FUT3 and FUT6, while the TRAIL-resistant cell lines, such as DLD-1 and HCT 116, show low expression of FUT3 and FUT6 [24,37]. Reduction in the number of fucosyl attachment sites by pretreatment with the Oglycosylation inhibitor bGalNAc led to decreased TRAIL sensitivity via DR5 in all three cell lines mentioned, as determined by us using TRAIL-death receptor specific variants.…”
Section: Discussionsupporting
confidence: 92%
“…Here we further show that this insensitivity is not related to a lack of surface expression levels of DR5, but to a specific lack of fucosylation. This finding is in line with earlier observations that TRAIL-sensitive colon adenocarcinoma cell lines show relatively high mRNA levels of FUT3 and FUT6, while the TRAIL-resistant cell lines, such as DLD-1 and HCT 116, show low expression of FUT3 and FUT6 [24,37]. Reduction in the number of fucosyl attachment sites by pretreatment with the Oglycosylation inhibitor bGalNAc led to decreased TRAIL sensitivity via DR5 in all three cell lines mentioned, as determined by us using TRAIL-death receptor specific variants.…”
Section: Discussionsupporting
confidence: 92%
“…Red-orange fluorescence was attributable to potential-dependent aggregation in the mitochondria. Green fluorescence, indicating the monomeric form of JC-1, appeared in the cytosol after mitochondrial membrane depolarization [48]. In the mPTP opening assay, calcein-acetoxymethyl ester (5 μM, cat.…”
Section: Measurement Of Mitochondrial Permeability Transition Pore (Mmentioning
confidence: 99%
“…For instance, it has been demonstrated that Nglycosylated DR4 was responsible for a strongest receptor response to the TRAIL attachment. 40 On the other hand, another study proves that an elevated expression of O-glycosylation of the DR5 correlates with higher sensitivity to TRAIL-mediated apoptosis in a large number of tumor cell lines. 41 Other works stipulated that both receptors are expressed simultaneously on the same cell and the binding of TRAIL necessitated only nanomolar affinity to be effective.…”
Section: Resultsmentioning
confidence: 95%
“…Although this assertion has been recently reversed, modification of DR4 or DR5 are often at the origin of the TRAIL‐sensitivity increase by promoting ligand‐induced receptor clustering and consequent caspase 8 activation. For instance, it has been demonstrated that N‐glycosylated DR4 was responsible for a strongest receptor response to the TRAIL attachment . On the other hand, another study proves that an elevated expression of O‐glycosylation of the DR5 correlates with higher sensitivity to TRAIL‐mediated apoptosis in a large number of tumor cell lines .…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation